Improvement in semipermeable membrane performance of wholly aromatic polyamide through an additive processing strategy. Issue 9 (8th February 2014) - Aiba, Motohiro; Tokuyama, Takahiro; Baba, Susumu; Matsumoto, Hidetoshi; Tomioka, Hiroki; Higashihara, Tomoya; Ueda, Mitsuru
ABSTRACT A new concept for the method to provide semipermeability in ultrathin and single‐component wholly aromatic polyamide membranes has been developed for the first time. It was found that water molecules could permeate through the membrane prepared not from polyamides containing flexible ether, bulky binaphthyl, or fluorene rigid units, but one with carboxylic acid groups under a reverse osmosis mode. However, the enhancement of water transport properties by introducing the hydrophilic group of polyamide was not substantial. Therefore, polyamide membranes were prepared from the solution containing aqueous additives in order to weaken hydrogen bonds between polymer chains and thereby to suppress the aggregation of the polymer chains. As a result, water flux was dramatically improved with slightly improved NaCl rejection. Our analyses based on attenuated total reflectance Fourier transform infrared spectroscopy and solid‐state carbon polarization and magic angle spinning nuclear magnetic resonance (13C CPMAS NMR) spectroscopy confirmed that the aggregation of polymer chains due to the hydrogen bonds among the amide linkages was suppressed by the co‐ordination of the aqueous additives to the amide linkage. The state of water in the membranes analyzed by differential scanning calorimetry also supported the formation of pores. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1275–1281